Evaluation of Petroleum Ether Extracts of Some Medicinal Plants Against Root Knot Nematode on Soybean - Devi*, L. Joymati. (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: The petroleum ether extracts of some medicinal plants Tectona grandis, Mussendra globra, Xylosoma longifolia, Ocimum sanctum and Melia azedarach were tested as seed soaking on soybean for pot experiment. The seeds were soaked in 100 ppm concentration for 24 hours and dry in sun light and seedling was done in sterilized soil. After proper inoculation of J2 of root knot nematode Meloidogyne incognita, different observation were taken after 75 days of inoculation and found that plants treated with petroleum ether extracts of M. azedarach were shown much improvement in plant growth rate and reduction in disease incidence when compared with other treated plants. Petroleum ether extracts of Tectona grandis was found least effective when compared with untreated but inoculated one.